Kehidupan Murid Kristus Berdasarkan 1 Petrus 3:8-17 - Eni Lestari (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2023)
The world is entering a new era, that's why we have to prepare a new social system as well. Many discussions lately talked about efforts to increase human resources. Likewise in the world of ministry, believers must be willing to improve their quality to respond those changes. A proper understanding of this ongoing era is necessarily needed to prepare well. Peter gave this important advice in his day, which is also very urgent for the church today. How should Christ's disciple live in this new era? This article was created to remind how disciples of Christ should live their lives, especially exploring the Bible in 1 Peter 3:8-17. The first part will examine aspects of personal life (faith in Christ, Christlike character, shunning evil and seeking peace). The second part is about the life of service which will describe the readiness to give accountability and to suffer for the truth.